2011
DOI: 10.1186/1472-6890-11-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different centrifugation conditions on clinical chemistry and Immunology test results

Abstract: BackgroundThe effect of centrifugation time of heparinized blood samples on clinical chemistry and immunology results has rarely been studied. WHO guideline proposed a 15 min centrifugation time without citing any scientific publications. The centrifugation time has a considerable impact on the turn-around-time.MethodsWe investigated 74 parameters in samples from 44 patients on a Roche Cobas 6000 system, to see whether there was a statistical significant difference in the test results among specimens centrifug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 7 publications
1
16
0
1
Order By: Relevance
“…Despite this, the influence of a shorter centrifugation time has been scantly investigated. 7 -10 Recently, Minder et al 11 reported on the effect of different centrifugation conditions on a broad range of chemistry and immunochemistry assays in human plasma. No significant difference was observed in the analytical outcome after whole blood was centrifuged according to the WHO guidelines (15 min at 2180 Â g 3 ) or for 10 min at 2180 Â g or 7 min at 1870 Â g. The data by Minder et al suggest that centrifugation time can be reduced from 15 to 7 min, a 47% decrease that, according to the authors, leads to a significantly faster intralaboratory TAT.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, the influence of a shorter centrifugation time has been scantly investigated. 7 -10 Recently, Minder et al 11 reported on the effect of different centrifugation conditions on a broad range of chemistry and immunochemistry assays in human plasma. No significant difference was observed in the analytical outcome after whole blood was centrifuged according to the WHO guidelines (15 min at 2180 Â g 3 ) or for 10 min at 2180 Â g or 7 min at 1870 Â g. The data by Minder et al suggest that centrifugation time can be reduced from 15 to 7 min, a 47% decrease that, according to the authors, leads to a significantly faster intralaboratory TAT.…”
Section: Discussionmentioning
confidence: 99%
“…La sangre de cada muestra fue dividida en dos partes, una de ellas se utilizó para realizar el hemograma, y el resto se centrifugó a 3000 rpm por 15 min a temperatura ambiente para la extracción del plasma. El producto fue almacenado en refrigeración (4°C) para definir su bioquímica sanguínea posteriormente (18).…”
Section: Methodsunclassified
“…Each sample was divided into two parts; one of which was used for hematology, and the rest was centrifuged at 3000 rpm for 15 min at room temperature to extract plasma. The product was refrigerated (4°C) to later define blood chemistry (18).…”
Section: Methodsmentioning
confidence: 99%
“…Unoptimized centrifugation can result in unnecessary over centrifuging (by virtue of waiting longer than needed) or material waste (by virtue of not recovering all of the material). This is well illustrated by several publications that show how well accepted clinical centrifugation protocols are sometimes longer than needed [ 7 9 ], lengthening diagnostic procedures and potentially adding to health care costs.…”
Section: Introductionmentioning
confidence: 99%